Pengaruh Model Argument-Driven Inquiry-STEM-EFA terhadap Peningkatan Scientific Reasoning Skills Siswa - Nadya Dewi Arofah Mochsif; Parno Parno; Lia Yuliati (Graduate School of Universitas Negeri Malang, 2021)
Abstract: This research examines the effect of the STEM-EFA integrated ADI model for improving students' scientific reasoning skills. The research was conducted in class XI of SMAN 8 Malang with 27 students participating. Learning is carried out by emphasizing practical activities, doing arguments, and making simple stove prototypes. The student’s enhancement of scientific reasoning skills was measured from the results of the pretest and posttest using two-tier questions. The analysis showed that there was a significant increase with p = 0.000. These results indicate that the STEM-EFA integrated ADI model influences increasing scientific reasoning skills. The N-Gain calculation of 0.34 indicates that the category of increasing students' scientific reasoning skills is classified as moderate.Abstrak: Penelitian ini mengkaji pengaruh model ADI terintegrasi STEM-EFA terhadap peningkatan kemampuan scientific reasoning skills siswa. Penelitian dilakukan di kelas XI SMAN 8 Malang dengan jumlah partisipan 27 siswa. Pembelajaran dilakukan dengan menekankan pada kegiatan praktikum, argumentasi, dan pembuatan prototipe kompor sederhana. Peningkatan kemampuan scientific reasoning skills siswa diukur dari hasil pretest dan posttest menggunakan soal two-tier. Analisis menunjukkan terdapat peningkatan yang signifikan dengan p = 0,000. Hasil ini menunjukkan bahwa model ADI terintegrasi STEM-EFA memberikan pengaruh terhadap peningkatan scientific reasoning skills. Perhitungan N-Gain sebesar 0,34 menunjukkan bahwa kategori peningkatan kemampuan scientific reasoning skills siswa tergolong sedang.